AN INVESTIGATION OF UNDERGRADUATE STUDENTS’ PERCEPTION IN USING GOOGLE CLASSROOM APPLICATION IN ELT TRAINING CLASSROOM - Indra Yoga Prawiro; Linda Yuliyah Ningrum (JELLT (Journal of English Language and Language Teaching), 2021)
Nowadays, many lecturers use various tools to support the online learning process, such as Moodle, Schoology, Edmodo, and Google Classroom. This study focuses on exploring the undergraduate students’ perceptions of Google Classroom’s implementation in online English Learning. With the case study design, seven undergraduate students from English Education Department in Wiralodra University participated in this study. The questionnaire and interview were used to collect the data, and both of them were analyzed qualitatively. The study results revealed that in terms of implementation, the Google Classroom application is an application that is easy to use, less effective in material explanation, and effective in the technic of administration and material management. Then, this study showed some positive impacts of the Google Classroom application. First, Google Classroom can record an effort of learning, material and assignment. The second, it provides quick access to collect an assignment, and The last, it minimizes the cost of learning. However, this study also revealed some negative impacts, such as trouble with an internet connection speed and screen display of google classroom. So, from the result of the study, it can be concluded that Google Classroom can be one of the application choices in teaching undergraduate students.